Lymphogranuloma venereum detected from the pharynx in four London men who have sex with men. (June 2013) - Dosekun, O; Edmonds, S; Stockwell, S; French, P; White, JA
Summary: Lymphogranuloma venereum (LGV) is an established cause of proctitis in men who have sex with men (MSM). Currently in the UK, testing for pharyngeal Chlamydia trachomatis (CT) is not routine, and LGV typing is usually only performed in patients with anorectal symptoms. We report four cases where LGV-associated CT DNA was detected from the pharynx in MSM, demonstrating that nucleic acid amplification testing (NAAT) can be used for detecting and typing pharyngeal CT infection. These cases also highlight other possible routes of infection for LGV, and add to the broad spectrum of clinical presentations associated with this infection.